Effect of Methylobacterium radiotolerans ED5-9 with Capability of Producing Indole-3-Acetic Acid (IAA) and 1-Aminocyclopropane-1-Carboxylic Acid Deaminase on the Growth and Development of Murdannia loriformis (Hassk.) Rolla Rao & Kammathy under In Vitro Condition - Prombunchachai, Thanawut; Nakaew, Nareeluk; Chidburee, Apichat; Siripun Sarin (Asian Health, Science and Technology Reports, 2017)
This study aimed to evaluate the production of 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase enzyme from endophytic Methylobacterium radiotolerans ED5-9, and to investigate the effects of M. radiotolerans ED5-9 on Murdannia loriformis, under tissue culture condition. M. radiotolerans ED5-9 was isolated from leaves of M. loriformis and cultured in vitro. It produced indole-3-acetic acid (IAA) with a concentration of 3.36 ± 0.20 µg/ml after incubation for 60 hr. Activity of ACC deaminase enzyme was observed at 365.05 ± 90.51 nmol of a-ketobutyrate/mg of protein/h. To test the effects of inoculation, the experiment was carried on by immersion of the explants of M. loriformis into M. radiotolerans ED5-9 suspension for 1, 3 and 5 min, and subsequently cultured on the MS medium in which 2 mg/l of IAA substance was used as the control. The results showed that duration time of the immersed explants in M. radiotolerans ED5-9 suspension for 5 min had the highest average number of shoots (6.00 ± 1.00 shoots per explants), root length (0.71 ± 0.26 cm) and dry weight (46.00 ± 5.40 mg). However, the above results of growth were similar to the growth of M. loriformis explants in the control. The results indicated the possible utilizing of M. radiotolerans ED5-9 can produce ACC deaminase enzyme and IAA to enhance growth and development of the M. loriformis explants under the in vitro condition.